Pengaruh Efektifitas Pembiayaan Murabahah Terhadap Tingkat Pendapatan Nasabah - Nuni Oktaviani (LPPM STAIS Dharma Indramayu, 2019)
Murabahah financing is financing with a sale and purchase agreement in a financial institution shown to the seller and buyer. The selling price is the purchase price plus the profit. The financial institution must state the actual price and state the profit determined according to the agreed percentage. Payment can be made by paying fixed installments according to the agreed amount until the specified time period. The main problem in this research is: